(-2xy^2)^2×(-2x^2y)^3×(-x^2 z)÷(2x^3y^2)=(4x^2y^4)×(-8x^6y^3)×(-x^2 z)÷(2x^3y^2)=(4x^2y^4)×(8x^6y^3)×(x^2 z)÷(2x^3y^2)=(4×8÷2)×x^(2+6+2-3)×y^(4+3-2)×z=16x^7y^5z
(-2xy^2)^2×(-2x^2y)^3×(-x^2 z)÷(2x^3y^2)
2个回答
相关问题
-
(2x)^3×(-2Y^3)÷16XY^2 (2X+Y+3Z)(2X+Y_3Z)
-
计算:(x|x^2-xy)^﹣3×(﹣x^2-2xy+y^2)﹣2÷(x^2|xy-y^2)^2=
-
(-x)^2×x^3×(-2y)^3+(-2xy)^2×(-x)^3×y
-
计算(1)x×(9x^3y-3xy^2)÷(-3x^2y)(2)((x+y)^2-(x-y)^2)÷(-4xy)(3)三
-
(x+y)(x-y)+(x-y)^2-(6x^2×y÷2y-2xy^2÷2y)其中x=-3,y=1/3
-
已知x:y=2:3,求(x^2-y^2/xy)÷[(x+y)×(x-y/x)^3]÷(x/y^2)
-
第一题:(3xy^2)^2+(-xy^3)×(-4xy) 第二题:(2x^3y)2×(-2xy)+(-2x^3y)^3×
-
先化简,再求值;(x^2y-x^3)\(x^2+2xy+y^2)÷x\(x-y)×(x+y)\(x^2-2xy+y^2)
-
x=6y,x-2×2=10(y-2z),x+2×6=3(y+6z)
-
2xy(½x2y-2y2x) (3x²y+4xy²-x³y³)×(-x